The Mediation Role Of Capital Structure And Profitability Moderation In The Relationship Between Liquidity And Company Value (Case Study Of Companies With Small-Mid Cap Liquid Index Listed On The Idx In The 2018-2023 Period) - Yasmin Atsilah; Wawan Ichwanudin; Intan Purbasari (Journal of Governance, Taxation and Auditing, 2026)
In this study, the researcher aims to provide new insights into whether liquidity can enhance firm value by employing capital structure as a mediating variable and profitability as a moderating variable. This research uses a quantitative approach with a causal design and utilizes secondary data obtained from TradingView, annual financial reports available on company websites, and the Indonesia Stock Exchange. The sampling method applied in this research is non-probability sampling with a purposive sampling technique, focusing on companies listed in the Small-Mid Cap Liquid Index on the Indonesia Stock Exchange for the 2018–2023 period. The data were then analyzed using SPSS version 25 through descriptive statistical analysis, followed by hypothesis testing using the PROCESS macro by Hayes. The findings of this study indicate that liquidity has a positive but insignificant effect on firm value; liquidity has a negative and significant effect on capital structure; capital structure has a negative and insignificant effect on firm value; capital structure is unable to mediate the relationship between liquidity and firm value; profitability cannot moderate the relationship between liquidity and firm value; profitability cannot moderate the relationship between capital structure and firm value; however, profitability can moderate the relationship between liquidity and firm value when capital structure is included as a mediating variable.